Antarctic icebergs: A significant natural ocean sound source in the Southern Hemisphere. (25th August 2014) - Matsumoto, Haru; Bohnenstiehl, DelWayne R.; Tournadre, Jean; Dziak, Robert P.; Haxel, Joseph H.; Lau, T.‐K. A.; Fowler, Matt; Salo, Sigrid A.
Abstract In late 2007, two massive icebergs, C19a and B15a, drifted into open water and slowly disintegrated in the southernmost Pacific Ocean. Archived acoustic records show that the high‐intensity underwater sounds accompanying this breakup increased ocean noise levels at mid‐to‐equatorial latitudes over a period of ∼1.5 years. More typically, seasonal variations in ocean noise, which are characterized by austral summer‐highs and winter‐lows, appear to be modulated by the annual cycle of Antarctic iceberg drift and subsequent disintegration. This seasonal pattern is observed in all three Oceans of the Southern Hemisphere. The life cycle of Antarctic icebergs affects not only marine ecosystem but also the sound environment in far‐reaching areas and must be accounted for in any effort to isolate anthropogenic or climate‐induced noise contributions to the ocean soundscape.